Dynamic routing for HTTP Adaptive VBR Video Streaming based on softwave defined networking - Phạm Hồng Thịnh; Hồ Văn Phi (My University, 2022)
Dynamic routing for HTTP Adaptive VBR Video Streaming based on softwave defined networking
Keywords: Định tuyến động; SDN; Video Streaming